Risk of esophageal cancer in achalasia cardia: A meta‐analysis. Issue 3 (8th February 2019) - Gillies, Clare L; Farrukh, Affifa; Abrams, Keith R; Mayberry, John F
Abstract : Introduction: The association between cancer of the esophagus and achalasia has long been recognized. However, it has also been recognized that cancers themselves can give rise to achalasia‐like syndromes. The risk of developing cancer is also a factor in assessing whether there is a potential role for surveillance in this disease. This paper uses published work to form the basis for a meta‐analysis of the risk of developing esophageal cancer among patients with pre‐existing achalasia. Methods: This paper considered cancer risk reported in a range of studies of achalasia published over a 50‐year period. Twenty‐seven potential studies were identified. In 16 reports, it was possible to extract information on both length of follow‐up and duration of achalasia so that person‐years duration (PYD) could be calculated. The analysis was stratified between cancers identified in the first year after diagnosis of achalasia and cancers identified in subsequent years. Results: From pooling the results of 16 studies, the incidence rate of esophageal cancer in achalasia patients was estimated to be 1.36 (95% CI: 0.56, 2.51) per 1000 person years. This is over 10 times higher than the general population incidence rates as reported by the lARC. Conclusions: Therefore, our meta‐analysis shows that achalasia is a major risk factor for the development of esophageal cancer. This is supported by the results from the time‐stratified analysis. Incidence of esophageal cancer per 1000 person years was lower in the first year after diagnosis of achalasia than in subsequent years. This is strong evidence against the idea that achalasia may be induced by esophageal cancer instead of vice versa. Abstract : This meta‐analysis shows a significant cancer risk in achalasia. This increases with time from initial diagnosis of the disease.